Dealing with Complexity: An Autopoietic View of the People's Planning Campaign, Kerala - ANGELIQUE CHETTIPARAMB (Planning Theory & Practice, Vol. 8, No. 4, 489-508, December 2007, 2007)
Complexity is integral to planning today. Everyone and everything seem to be interconnected, causality appears ambiguous, unintended consequences are ubiquitous, and information overload is a constant challenge. The nature of complexity, the consequences of it for society, and the ways in which one might confront it, understand it and deal with it in order to allow for the possibility of planning, are issues increasingly demanding analytical attention. One theoretical framework that can potentially assist planners in this regard is Luhmann's theory of autopoiesis. This article uses insights from Luhmann's ideas to understand the nature of complexity and its reduction, thereby redefining issues in planning, and explores the ways in which management of these issues might be observed in actual planning practice via a reinterpreted case study of the People's Planning Campaign in Kerala, India. Overall, this reinterpretation leads to a different understanding of the scope of planning and planning practice, telling a story about complexity and systemic response. It allows the reinterpretation of otherwise familiar phenomena, both highlighting the empirical relevance of the theory and providing new and original insight into particular dynamics of the case study. This not only provides a greater understanding of the dynamics of complexity, but also produces advice to help planners implement structures and processes that can cope with complexity in practice